(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tourism has grown from the pursuits of a privileged few to a mass movement of people, with the urge to discover the unknown, to explore new and strange places, to seek changes in environment. Tourism as a service industry is international in character both in terms of demand and supply. Tourism is not merely leisure or entertainment or physical invigoration or mental rejuvenation. It also serves as a potent instrument for eliminating poverty, for ending employment, for promoting dialogue among civilizations and for providing channels in which streams of different culture could meet and mingle and create a new ethic-scape on which a fair, just humane and enlightened order could be built for the entire human race. This paper reflects, a geographical study on tourism of India.